2014
DOI: 10.1007/s11604-014-0291-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of IMRT and VMAT plans with different energy levels using Monte-Carlo algorithm for prostate cancer

Abstract: VMAT plans were found to be dosimetrically equivalent to IMRT plans for prostate cancer patients, with better rectum and bladder sparing and fewer MUs required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…The decrease in monitor units for the 10 MV plans indicates that the higher energy beams were able to achieve equivalent target dose coverage more efficiently than the lower energy beams. This reduction in MUs for higher energy beams agrees with results found by other groups that have compared 6 MV with 10, 15, and 18 MV VMAT and IMRT plans for prostate and cervix cancer cases 34, 35, 36…”
Section: Discussionsupporting
confidence: 90%
“…The decrease in monitor units for the 10 MV plans indicates that the higher energy beams were able to achieve equivalent target dose coverage more efficiently than the lower energy beams. This reduction in MUs for higher energy beams agrees with results found by other groups that have compared 6 MV with 10, 15, and 18 MV VMAT and IMRT plans for prostate and cervix cancer cases 34, 35, 36…”
Section: Discussionsupporting
confidence: 90%
“…For small bowel, the Sale study reported that there was no significant reduction in the volume of small bowel receiving lower doses in VMAT plans. Onal et al (34) also reported that there was no significant irradiation dose differences about D50 and Dmax between IMRT and VMAT in sigmoid colon.…”
Section: Discussionmentioning
confidence: 95%
“…Onal et al . [ 27 ] also compared IMRT and VMAT plans with different energy levels 6, 10, and 15 MV using Monte-Carlo algorithm for prostate cancer. They found the significant difference only in number of MUs for 10 MV and 6 MV plans, as they did not calculate GM, EVI, and low dose volume of normal tissue.…”
Section: Discussionmentioning
confidence: 99%